Composite sandwich panels subjected to impact of a foreign body - Zhu, Shengqing. (2013)
This dissertation presents the experimental, numerical and analytical investigations on the impact behaviour of composite sandwich panels. The objectives of this research are to predict the low-velocity impact response and damage in composite sandwich panels, and to characterize the energy absorbed by the structure.